Gluconeogenesis and glucose replacement rate during long-term fasting of Japanese quails - Sartori, DRS; Kettelhut, I. C.; Veiga, JAS; Migliorini, R. H. (Elsevier B.V., 1996)
Gluconeogenic activity and kinetic parameters of glucose metabolism were estimated during the different phases of prolonged food deprivation in quails. Gluconeogenic activity, estimated from the rate of increase of incorporation of (HCO3-)-C-14 into circulating glucose, was significantly higher in fasted quails than in fed birds, whatever the period of food deprivation. However, gluconeogenic activity during phase II, although higher than in the fed state, was significantly lower than in quails fasted for 2 days (phase I) or in those on the final (phase III) period of starvation. Gluconeogenic activity did not differ significantly in birds from phases I and III. Rates of glucose replacement, estimated with [6-H-3]-glucose, were very high (20.5 mg . kg(-1). min(-1)) in fed quails and were markedly reduced (to about 42% of fed values) by fasting, no difference being observed between quails fasted for 2 and 5 days. Because of the poor condition of the birds, glucose replacement rates could not be measured during phase III. The present data are the first to provide direct evidence for the changes in gluconeogenesis which occur during prolonged food deprivation.
Keywords: gluconeogenic activity; glucose replacement rate; long-term fasting; quails